Understanding public health risk from unsafe dry fish consumption in Bangladesh. - Mahdi Al Hasan Rahat; Anik Saha; Mehedy Hasan Abir; A S M Nafis Sadekeen; Shahneaz Ali Khan; Sukanta Chowdury (PLoS ONE)
Dried fish holds a significant place in the Bangladeshi diet particularly for people living in coastal regions. However, there is a growing concern regarding its adverse effects on human health, as it contains high levels of illegal preservatives, heavy metals, and other harmful substances. In this study, we aimed to explore the current knowledge, attitudes, and practices regarding health hazards due to unsafe dried fish consumption among people across the country. We conducted a cross-sectional study among consumers to assess their knowledge, attitudes, and practices about the health risks associated with consuming hazardous dried fish. We interviewed a total of 415 participants, of whom 52.8% were male; the majority were students (55.9%), aged between 18 and 30 years (63.9%), and living in urban areas (81.7%). Most of the participants (60.7%) had less accurate knowledge of the health hazards of unsafe dry fish, 92.8% had more positive attitudes to buying safe dry fish, and 26.8% used unsafe dry fish more frequently. Many respondents were unaware of the presence of harmful substances in dried fish, such as illegal pesticides (66.5%), microplastics (77.6%), and heavy metals (67.4%). A significant number of participants (13%) reported that they had a history of cancer in any of their family members. Many individuals (57.4%) were not familiar with the proper storage and preparation methods of dry fish. The majority of participants (81.4%) strongly prefer packed dried fish. Most of the respondents (67.7%) agreed to participate in awareness programs. Female consumers were more likely to have more accurate knowledge (AOR = 1.53; 95% CI = 1.03-2.29, p = 0.0.37) than males, and participants whose present residence were in rural were more likely to have accurate knowledge (AOR = 2.64; 95% CI = 1.30-5.36, p = 0.007) than those whose present residence were in urban or semi-urban areas. A targeted education campaign focused on improving awareness of the risks associated with eating unsafe dry fish is needed, particularly in coastal areas.